Effect of ytterbium doping concentration on structural, optical and photocatalytic properties of TiO2 thin films. Issue 17 (1st December 2017) - Pérez, J.A. Borrego; Courel, Maykel; Pal, Mou; Delgado, F. Paraguay; Mathews, N.R.
Abstract: Ytterbium (Yb) doped TiO2 thin films have been synthesized by sol-gel spin-coating technique. Films with different Yb concentrations such as 0.5, 1, 2, 4 wt% were deposited and the impact of the dopant concentration on their physicochemical properties was evaluated. The films were characterized by X-Ray diffraction, transmission electron microscopy, Raman spectroscopy, UV–Vis transmittance spectroscopy and photoresponse. The results showed that the incorporation of ytterbium modified the properties of TiO2 films. The photocatalytic efficiency of TiO2 :Yb films was determined using methylene blue (MB) as the generic pollutant. Compared to undoped TiO2, 1 wt% Yb doped films exhibited higher photocatalytic activity toward MB degradation under UV light. When the amount of Yb dopant concentration was increased, there was a negative effect on the photosensitivity and photocatalysis.